Radial turbine sound and noise characterisation with acoustic transfer matrices by means of fast one-dimensional models. (April 2021) - Torregrosa, Antonio; García-Cuevas, Luis Miguel; Inhestern, Lukas Benjamin; Soler, Pablo
Estimating correctly the turbine acoustics can be valuable during the engine design stage; in fact, it can lead to a more optimised design of the silencer and aftertreatment, as well as to better prediction of the scavenging effects. However, obtaining the sound and noise emissions of radial turbocharger turbines with low computational costs can be challenging. To consider these effects in a time-efficient manner, the acoustic response of single-entry radial turbines can be characterised by means of acoustic transfer matrices that change with the operating conditions. Exploiting the different time-scales of the acoustic phenomena and the change in the operating point of the turbine, lookup tables of acoustic transfer matrices can be computed. Then, the obtained characterisation can be used in mean-value engine models. This article presents a method for generating these lookup tables by means of fast one-dimensional simulations of thoroughly validated fidelity, in terms of both acoustics and extrapolation capabilities. Due to the inherent behaviour of radial turbines, the number of computations needed to fill the lookup tables is relatively small, so the method can be used as a simple preprocessing phase before mean-value simulation campaigns.